Holocene relative sea-level variations and archeological implications, Abu Dhabi western region, United Arab Emirates - Pavlopoulos, Kosmas (2020)
New results from fieldwork in the western region of the Emirate of Abu Dhabi showed meaningful differences in relative sea-level variations during Holocene and recorded unknown late marine highstands. These dynamics may have induced important environmental changes and affected human settlement. Surveys have been carried out in the Emirate of Abu Dhabi in order to construct local sea-level variations. These results rely on identifying, characterizing, and dating sea-level indicators and particularly beachrocks. Two main areas were studied: Ghagha island and Ras Khumays peninsula. Data obtained from our surveys highlight significant differences and suggest local processes that need to be understood. From an archeological perspective, this work helps to better understand human settlement dynamic through the Holocene.